Critical Waste Reduction in Flexible Packaging Printing Process Using Lean-DMAIC Approach - Mohamad Yayan Ramadani; Dini Retnowati; Ahmad Fatih Fudhla (Heuristic, 2026)
The printing process in flexible packaging manufacturing is highly sensitive to operational inefficiencies, as it involves machine setup, color adjustments, material handling, inspection activities, and coordination across departments. Inefficiencies in this process may lead to defects, work-in-process accumulation, increased waiting time, and reduced performance of the production flow. This study aims to identify, prioritize, and reduce critical waste in the printing process of a flexible packaging manufacturing system using the Lean-DMAIC approach. A quantitative case study was conducted using process flow, cycle time, lead time, production, and waste occurrence data collected from January to December 2025. In the define stage, Value Stream Mapping (VSM) was used to describe the production flow and identify process inefficiencies. In the measure stage, seven types of waste were quantified and prioritized using Pareto analysis. The analysis stage used Root Cause Analysis (RCA) and Failure Mode and Effects Analysis (FMEA) to identify root causes and assess risk levels using the Risk Priority Number (RPN). The results show that defects, inventory, and waiting are the dominant wastes, contributing to approximately 80% of total waste. Defects have the highest RPN value of 567, indicating the most critical problem. The proposed improvement actions reduced defect waste from 13.20% to 6.15%, inventory waste from 11.25% to 4.30%, and waiting waste from 6.49% to 3.95%. These findings indicate that integrating Lean-DMAIC, VSM, Pareto analysis, RCA, and FMEA provides a structured, effective approach to reducing critical waste in flexible packaging printing operations.